The relationship between innovation management and the leader’s intellectual arousal in the pharmaceutical companies - Mohammed, Sanaa Mostafa Mohammed (International Journal of Management and Sustainability, 2023)
The methodology for this study was quantitative research. A total of 319 employees who completed an online survey examining innovation management (IM) and the leader's intellectual arousal (LIA) were included in the sample. The results revealed that there is a positive, statistically significant relationship between innovation management and the leader’s intellectual arousal. IM has a crucial role in fostering and encouraging LIA. The study offered a thorough insight into the leader's personal conduct as seen by followers. This study added new scientific understanding to a subject that had previously only been studied by subordinates, as well as new information to the notion of innovation management. The results show that enhancing innovation management is an effective strategy to raise a leader's intellectual arousal, which could ultimately increase both individual and organizational performance. The need for courage, justice, wisdom, and humanity in the leader as a necessary condition for knowledge management efficacy is the study's main point of emphasis.